SOME PROPERTIES OF J -HAUSDORFF, J -REGULAR AND J -NORMAL SPACES (2018)
In this paper we present new properties about the J - Hausdorff, J -regular and J -normal spaces, introduced recently by Suriyakala-Vembu. Additionally we introduce the J -Urysohn spaces, an intermediate concept between the Urysohn spaces and the J - Hausdorff spaces. We present some of its properties.